Ironic Deliberations: A (Regrettably Incomplete) Response to Fischer, Nelkin, and Vargas. - Doris, John M. (Social Theory & Practice, 2018)
The author discusses the comment on his book "Talking to Our Selves" by John Martin Fischer, Dana Kay Nelkin, and Manuel R. Vargas. It mentions problems associated with morally responsible agency are among the most incorrigible in philosophy and expression of values that need not be threatened by self-ignorance, so neither need agency. It also mentions philosophical theorizing and evidence from psychology cannot be used to upend the evidence of experience.